Mass Spectrometry Offers Insight into the Role of Ser/Thr/Tyr Phosphorylation in the Mycobacteria - Calder, Bridget; Albeldas, Claudia; Blackburn, Jonathan M.; Soares, Nelson C. (Frontiers in Microbiology, 2016)
Phosphorylation is a post translational modification which can rapidly regulate biochemical pathways by altering protein function, and has been associated with pathogenicity in bacteria. Once engulfed by host macrophages, pathogenic bacteria are exposed to harsh conditions and must respond rapidly in order to survive. The causative agent of TB, Mycobacterium tuberculosis, is unusual amongst the bacteria because it can survive within the host macrophage for decades in a latent state, demonstrating a remarkable capacity to successfully evade the host immune response. This ability may be mediated in part by regulatory mechanisms such as ser/thr/tyr phosphorylation. Mass spectrometry-based proteomics has afforded us the capacity to identify hundreds of phosphorylation sites in the bacterial proteome, allowing for comparative phosphoproteomic studies in the mycobacteria. There remains an urgent need to validate the reported phosphosites, and to elucidate their biological function in the context of pathogenicity. However, given the sheer number of putative phosphorylation events in the mycobacterial proteome, and the technical difficulty of assigning biological function to a phosphorylation event, it will not be trivial to do so. There are currently six published phosphoproteomic investigations of a member of mycobacteria. Here, we combine the datasets from these studies in order to identify commonly detected phosphopeptides and phosphosites in order to present high confidence candidates for further validation. By applying modern mass spectrometry-based techniques to improve our understanding of phosphorylation and other PTMs in pathogenic bacteria, we may identify candidates for therapeutic intervention.